Groupthink Phenomenon as a Common Occurrence in Juvenile Gangs. (21st May 2015) - Caya, Sinan
Abstract: In this presentation, groupthink phenomenon is defined. Its symptoms specified in the related literature are cited. Then, a typical youth gang is related to each of those specific symptoms. The result depicts a high probability that such a gang may fall into groupthink, indeed!